Relatório de Estágio Profissional "Ensinar Aprendendo" - Marcelo David da Cruz Torres (2018)
The current Practicum Report provides, in a reflexive, founded and critical way, a perspective of the academic education that I went through in the last six years of University, more specifically the Practicum Training which is a curricular unit included in the 2nd year of the 2nd cycle in Physical Education Teaching in Primary and Secondary School Levels of the Faculty of Sports of the University of Porto. This Practicum took place in the Secondary School Filipa de Vilhena and in the Group of Schools Pêro Vaz de Caminha and it was guided and supervised by an Advisor-Teacher (from the Faculty of Sports of University of Porto) a Cooperative Teacher (from the Secondary School Filipa de Vilhena) and a Co-Cooperative Teacher (from the Group of Schools Pêro Vaz de Caminha). The presented document is divided into 6 chapters. 1)Introduction: deals with the framework of the Practicum Training; 2) Personal Framework: refers to my personal and professional background and points out my inicial expectations and understandings related to the Practicum Training; 3) Professional Practice Framework: Includes the institutional framework, presenting the school and the classes where the Practicum tool place; 4)Execution of the Professional Practice: refers to performance areas 1,2 and 3. Area 1 includes the Conception process, planning, execution and evaluation of all the teaching process. Area 2 refers to the school activities that were developed. Area 3 is dedicated to the research study; 5) Final thoughts and Future Perspectives. Focuses on reflecting about the whole year of Practicum, personal and professional evolution and accounts for future expectat